Corrosion mechanism of Ti2AlC MAX phase coatings under the synergistic effects of water vapor and solid NaCl at 600 °C. (November 2021) - Wang, Zhenyu; Ma, Guanshui; Li, Zhongchang; Ruan, Haitao; Yuan, Jianghuai; Wang, Li; Ke, Peiling; Wang, Aiying
Abstract: The corrosion behavior of Ti2 AlC MAX phase coatings coated on 1Cr11Ni2W2MoV substrates in NaCl deposit in water vapor at 600 °C has been fully investigated. The results demonstrated that the substrates underwent serious corrosion, but the coatings performed better. The mass gain per unit area of coatings was less than 1/6 of substrates, because of the formed compact and uniform corrosion scale. Such dense corrosion scale was composed of Na x Ti y O z fine grains with the size of 11 ± 0.4 nm and amorphous Al2 O3 phases which self-healed the generated defects during corrosion, benefiting from the novel layered structure of MAX phase. Graphical Abstract: ga1 Highlights: Dense and high-purity Ti2 AlC coatings were fabricated by a facile two-step technique. The mass gain per unit area of coatings was less than 1/6 of 1Cr11Ni2W2MoV substrates. Corrosion mechanism of Ti2 AlC coatings under NaCl-H2 O was completely investigated. Defects of corrosion scale were self-healed during corrosion by inert Al2 O3 tissue. Weakly-boned Al of Ti2 AlC coatings essentially favored their corrosion resistance.